Antibacterial Activity and Determination of Total Phenol and Flavonoid of Carica papaya L. Ethanol Extract - Karo-Karo, Sry Ulina; Arianto, Anayanti; Salim, Emil (Publisher Cv. Inara, 2023)
Infectious diseases are Indonesia's most common. Antibiotics are used to treat infections. Medicine needs new antibiotics due to antibiotic resistance. Antibiotics from plants are possible. Papaya leaf carpain alkaloids may be antibacterial. This study determined papaya leaf compound content, flavonoids' total phenol content, and the optimal concentration of papaya leaf ethanol extract that inhibits Staphylococcus aureus and Pseudomonas aeruginosa. The first stages of the research were the maceration of papaya leaf extract with 96% ethanol solvent, the phytochemical screening test (alkaloid, flavonoid, saponin, tannin, and steroid and triterpenoid tests), total phenol and total flavonoids tests, and the paper disc antibacterial activity test. Alkaloids, flavonoids, glycosides, tannins, steroids, and saponins were found in papaya leaf ethanol extract. Papaya leaf ethanol extract has 59.05 mgQE/g flavonoids and 56.80 GAE/g phenols. The antibacterial activity test of papaya leaf ethanol extract measured the diameter of the inhibitory zone on Staphylococcus aureus and Pseudomonas aeruginosa. Alkaloids, flavonoids, glycosides, tannins, steroids, and saponins were found in papaya leaf ethanol extract. Papaya leaf ethanol extract has 59.05 mgQE/g flavonoids and 56.80 GAE/g phenols. Papaya leaf ethanol extract had the best inhibition zone diameter for Staphylococcus aureus at 150 mg/mL (12.85 mm) and Pseudomonas aeruginosa at 150 mg/mL (13.10 mm).